Confrontation and Beyond: Examining a Stigmatized Target's Use of a Prejudice Reduction Strategy. Issue 2 (February 2015) - Focella, Elizabeth S.; Bean, Meghan G.; Stone, Jeff
Abstract What can stigmatized individuals do to reduce stereotyping, prejudice, and discrimination when they interact with a biased individual? This paper reviews the social psychological literature that examines how targets can be active agents of prejudice reduction for themselves and their group. The extant literature indicates that a target's direct confrontation of bias can reduce prejudice and discrimination against the target's group but that this strategy can also backlash in the form of increased prejudice and discrimination against the target. Other research indicates that presenting a common‐identity, self‐enhancing feedback, and a self‐affirmation can reduce bias against the target but that they may not reliably change bias against the target's group. We conclude by discussing the need for research on the processes by which stigmatized targets decide to use a given bias‐reduction strategy and on the processes by which specific strategies are effective, either alone or in combination, when delivered by a stigmatized target.